PROBLEMATIKA PENDAFTARAN TANAH WAKAF (STUDI DI KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG) - RAHMAT PARLAUNGAN SIREGAR (PREMISE LAW JURNAL, 2014)
ABSTRACT Wakaf, based on the Islamic Law, is submitting a plot of land or other objects which can be used by Moslems without damaging and wearing out them; they are given to a person or a legal entity for the benefit of all Moslems. On the other hand, wakaf, based on the Agrarian Law, is the transfer of title permanently. The consequence is that the land is permanently institutionalized, and it cannot be transferred to other parties, in the form of buying and selling, transferring, gift, etc., unless there is legal basis for its validity. The result of the research showed that the problems of the registration of wakaf land (A Case Study in Percut Sei Tuan Subdistrict, Deli Serdang District) were as follows: 1) people’s lack of understanding in Percut Sei Tuan Subdistrict, especially about the registration and the certification of wakaf land; they believe that when the wakaf land has been reported to the Religious Affairs Office/Official Empowered to Draw up Wakaf Avowal (PPAIW), there will be no problem anymore, 2) Wakaf cannot indicate legal basis for a wakaf land; therefore, the National Land Board Office cannot issue the certificate for the land although it has been avowed in the Religious Affairs Office (KUA) by the Official Empowered to Draw up Wakaf Avowal, and 3) the lack of personnel who handle wakaf land in the Religious Affairs Office and in the National Land Board Office so that there are a lot of wakaf lands which have not been processed, either in its avowal or its registration in the National Land Board Office. The role of the National Land Board in registering wakaf land is as the provider, place for complaint, information about land cases, the settlement of land dispute, and legal act in the implementation of the Court’s Ruling. Meanwhile, the role of KUA in registering wakaf land is as the motivator, facilitator, regulator, and public service. Keywords: Wakaf, Problems, Registration of Wakaf Land